2016
DOI: 10.1002/ab.21651
|View full text |Cite
|
Sign up to set email alerts
|

Pathways to romantic relational aggression through adolescent peer aggression and heavy episodic drinking

Abstract: Adolescent peer aggression is a well-established correlate of romantic relational aggression; however, the mechanisms underlying this association are unclear. Heavy episodic drinking (or "binge" alcohol use) was examined as both a prior and concurrent mediator of this link in a sample of 282 12-18 year old interviewed four times over 6 years. Path analyses indicated that early peer relational and physical aggression each uniquely predicted later romantic relational aggression. Concurrent heavy episodic drinkin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 72 publications
(114 reference statements)
0
3
0
Order By: Relevance
“…This trend was particularly evident among girls who drank five or more alcoholic drinks in one sitting when compared to girls who did not report drinking alcohol, as they were around twice as likely to report physical DRV victimisation and perpetration. Nevertheless, previous Canadian longitudinal research with 12 to 18 year olds demonstrated that although peer relational and physical abuse predicted DRV perpetration, binge drinking only mediated the link between early peer physical abuse and future DRV perpetration, and not early peer relational abuse [65]. Given the diversity of drinking cultures internationally [66], further longitudinal and qualitative studies are needed to explore the relationship between alcohol, DRV, and bullying among children and young people in the UK.…”
Section: Discussionmentioning
confidence: 96%
“…This trend was particularly evident among girls who drank five or more alcoholic drinks in one sitting when compared to girls who did not report drinking alcohol, as they were around twice as likely to report physical DRV victimisation and perpetration. Nevertheless, previous Canadian longitudinal research with 12 to 18 year olds demonstrated that although peer relational and physical abuse predicted DRV perpetration, binge drinking only mediated the link between early peer physical abuse and future DRV perpetration, and not early peer relational abuse [65]. Given the diversity of drinking cultures internationally [66], further longitudinal and qualitative studies are needed to explore the relationship between alcohol, DRV, and bullying among children and young people in the UK.…”
Section: Discussionmentioning
confidence: 96%
“…Continued alcohol use by adolescent girls puts them at higher risk for brain damage and behavioral problems in the future. The impact of drinking on adolescent girls’ development is significant and has been linked to various public health problems, such as anxiety, risky sexual decision-making, and drug use ( Woodin et al, 2016 ; Waterman et al, 2019 ; Lee and Feng, 2021 ). Our results suggest that cultivating adolescent girls’ PGI may be a possible intervention for addressing these issues.…”
Section: Discussionmentioning
confidence: 99%
“…Taking into account the aforementioned factors, it is likely that adolescent drinking in China will become a significant social and public problem, and may be associated with various adverse behavioral and mental outcomes in Tao et al 10.3389/fpsyg.2023.1199285 Frontiers in Psychology 02 frontiersin.org adolescents (eg. risk of sexual behavior, interpersonal violence, criminality, depression and anxiety) (Woodin et al, 2016;Waterman et al, 2019;Lee and Feng, 2021). Except of the negative impact on adolescent health, there is also a certain possibility that alcohol use may affect the brain development of adolescent individuals, adolescent neurons are more vulnerable than adult neurons to the effects of alcohol, even after a single dose (Mira et al, 2020).…”
Section: Introductionmentioning
confidence: 99%